2020
DOI: 10.3892/mmr.2020.11517
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering potential differentially expressed miRNAs and targeted mRNAs in myocardial infarction based on integrating analysis

Abstract: Myocardial infarction (Mi) is one of the leading causes of death globally. The aim of the present study was to find valuable micrornas (mirnas/mirs) and target mrnas in order to contribute to our understanding of the pathology of Mi. mirna and mrna data were downloaded for differential expression analysis. Then, a regulatory network between mirnas and mrnas was established, followed by function annotation of target mrnas. Thirdly, prognosis and diagnostic analysis of differentially methylated target mrnas were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 89 publications
2
4
0
Order By: Relevance
“…In the present study, the JASPAR database was used to predict the binding sites between PDE4B promoter and JDP2, a transcription factor that is differentially expressed in patients with MI (38). In view of the critical regulatory role of JDP2 in impaired cardiac function (17), the present study also confirmed that JDP2 was upregulated in H9c2 cells exposed to H/R, and verified the interaction between JDP2 and the PDE4B promoter region.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, the JASPAR database was used to predict the binding sites between PDE4B promoter and JDP2, a transcription factor that is differentially expressed in patients with MI (38). In view of the critical regulatory role of JDP2 in impaired cardiac function (17), the present study also confirmed that JDP2 was upregulated in H9c2 cells exposed to H/R, and verified the interaction between JDP2 and the PDE4B promoter region.…”
Section: Discussionsupporting
confidence: 70%
“…To identify the DEcircRNAs-DEmiRNAs-DEmRNAs regulatory relationships, we performed the prediction of circRNA–miRNA and miRNA–mRNA interactions based on the popular online tools, and then constructed a ceRNA network following the “ceRNA network hypothesis”. In this ceRNA network, previous studies have confirmed that miR-3194-3p/AQP1 ( 43 ), miR-1246/AXIN2 ( 44 ), miR-326/E2F2 ( 45 ), miR-326/CDCA5 ( 46 ), and miR-17-3p/RGS2 ( 47 ), etc, interaction relations play important roles in the occurrence and development of various cancers. Notably, these researches also to some extent reflect the veracity of the predicted ceRNA network in the current study.…”
Section: Discussionsupporting
confidence: 55%
“…[39] hsa-miR-27a-3p and hsa-miR-335-5p were crucial in IS, whereas hsa-miR-34a-5p was crucial in MI. [40,41] The above information may reveal some unique mechanisms underlying the diseases, suggest new disease markers, and provide a possible basis for predicting IS and MI, as well as identify potential therapeutic targets. The prediction of drugs may have a role in disease prevention.…”
Section: Discussionmentioning
confidence: 99%